Preliminary Clinical Results and Mechanical Behavior of a New Double-Layer Carotid Stent. (August 2015) - Wissgott, Christian; Schmidt, Wolfram; Brandt, Christoph; Behrens, Peter; Andresen, Reimer
Purpose: To evaluate the in vitro mechanical and clinical implant behavior of a next-generation double-layer stent designed for the carotid artery.Methods: The new double-layer CASPER-RX stent was implanted in 12 patients (median age 69 years; 8 men) with high-grade symptomatic internal carotid artery stenoses (mean 82%). In the in vitro experiments, the CASPER-RX stent (8-×40-mm model) was investigated with respect to its radial force on expansion and the bending stiffness of the stent system and of the stent in its expanded state, as well as the collapse pressure in a thin, flexible sleeve. The wall adaptation of the expanded stents was assessed by fluoroscopy after release in a step and curve model.Results: Technical success was achieved in all patients without complications; there was no peri- or postinterventional stroke and no stroke or restenosis after 6 months. In the experimental studies, the bending stiffness of the stent on the delivery system (154.9 N mm 2 ) was significantly lower than when expanded in a 7-mm flexible tube (467.4 N mm 2 ). The radial force on expansion of the stent to 7 mm was low (0.011 N/mm). The collapse pressure was relatively high (0.56 bar) as a result of the stent's particular stent structure. The stent exhibited significant foreshortening of 27.6%. The conformability to the wall in the step model was relatively smooth; in the curve model, straightening occurred with consecutive slight stenosis.Conclusion: The first clinical results showed a safe implantation behavior without the occurrence of any ischemia. The structure of the new CASPER-RX stent creates an acceptable flexibility, low radial force, and high collapse pressure. The large foreshortening during implantation should be considered as well as the higher bending stiffness, especially when used in elongated carotid arteries.